Implementation of Internal Quality Control in Clinical Laboratories of Portuguese Speaking Countries - Pinto, Mariana (2023)
ProMeQuaLab (Laboratory Quality Improvement Project for Portuguese Speaking Countries) is an ongoing project started in 2015 aiming to improve the quality of laboratory results in Portuguese Speaking countries ( It focuses on training in laboratory quality control, implementation and monitoring of quality indicators, and the organisation of a biennial congress. In 2023 within the scope of ProMeQuaLab and in collaboration with the National Health Institute Doctor Ricardo Jorge ( and the Faculty of Pharmacy of University of Lisbon, the Master's thesis "Development of tools and documentation for implementation of laboratory Quality Control in Portuguese Speaking countries" is being carried out. AIMS: Development and application tools for implementation of Internal Quality Control in the areas of Clinical Chemistry and Haematology, in PLP laboratories, from February to August 2023